The importance of new technologies and entrepreneurship in business development: in the context of economic diversity in developing countries the impact of new technologies and entrepreneurship on business development - Alareeni, Bahaaeddin; Hamdan, Allam; Elgedawy, Islam (Switzerland Springer, 2021)
This book introduces the students, researchers and practitioners into the subject and enabling technologies and applications pertaining to of technology, entrepreneurship and business development through research articles, case studies etc. It is primarily intended for academic purposes for learners of computer Science, management, accounting and information systems disciplines, economics,- entrepreneurship. Publishing chapters in the book is new innovative idea to spread the book in the Middle East and Arab countries and make the book achieve more sales. As many students in all levels, graduates and undergraduates in addition to research, professionals are not able to get sufficient resources because of the language concern.
Electronic reproduction
Keywords: Business mathematics